1994
DOI: 10.1364/ao.33.006315
|View full text |Cite
|
Sign up to set email alerts
|

Infrared evanescent-absorption spectroscopy with chalcogenide glass fibers

Abstract: We have used telluride glass fibers fabricated in house to measure the evanescent-absorption spectra of water, methanol, ethanol, isopropanol, acetone, ethanoic acid, hexane, and chloroform. Furthermore, detection limits of less than 2 vol. % solute were obtained for mixtures of water and methanol, ethanol, isopropanol, acetone, and ethanoic acid. Techniques to reduce the detection limits are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 14 publications
0
27
0
3
Order By: Relevance
“…Previous studies using either unclad, or removed cladding, multimode chalcogenide fibres for FEWS sensing, with core diameters ranging from 100 to 400 m, have been reported extensively [1,3,8,9,[31][32][33][34]. It is also known that by tapering down a fibre with sub-wavelength features can also improve FEWS sensing since large proportion of light cannot be confined in to the fibre core which propagates along the fibre surface [18,19].…”
Section: Analysis Of Optical Modes In the Ge-te-se Fibrementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies using either unclad, or removed cladding, multimode chalcogenide fibres for FEWS sensing, with core diameters ranging from 100 to 400 m, have been reported extensively [1,3,8,9,[31][32][33][34]. It is also known that by tapering down a fibre with sub-wavelength features can also improve FEWS sensing since large proportion of light cannot be confined in to the fibre core which propagates along the fibre surface [18,19].…”
Section: Analysis Of Optical Modes In the Ge-te-se Fibrementioning
confidence: 99%
“…Knight et al explained the principle of anti-resonant reflecting optical waveguide (ARROW) using silica materials and demonstrated a discontinuous transmission window between 3 and 4 m. The current limit is the difficulties in using other infrared glasses for fabricating such ARROW fibres, for which we believe the transmission and spectroscopic properties may be further improved, provided the glass material used exhibits the extended infrared transmission beyond the current range of solid-core silica. Unlike ARROW design, solid core-clad mid-infrared fibres using heavy metal oxide and chalcogenide glasses have demonstrated the usefulness in terms of accessing the mid-IR for chemical/biological sensing [1,[3][4][5][6][7][8]. Using such solid core fibre structures, a number of chemical species (benzene (C6H6) [1], toluene (C7H8) [1], sulfuric acid (H2SO4) [3], methanol (CH3OH) [4], methane (CH4) [4], ethanol (C2H5OH) [5], acetone ((CH3)2CO) [6][7][8] were analyzed and reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7203 72030I-5 In these films, the variance in composition among the glass types has a significant impact on the magnitude of the refractive index change. It was found that As 36 Ge 6 S 58 had a small negative induced refractive index change (Δn) of -0.005, whereas As 42 S 58 , and As 36 Sb 6 S 58 exhibited a large positive Δn of 0.06 and 0.09 respectively for 10x10 6 pulses per spot. However, the relationship between induced photo-expansion (density change) and refractive index change is not direct.…”
Section: Waveguide Fabrication and Characterizationmentioning
confidence: 99%
“…However, the use of such materials limits the functionality of the fabricated devices in the optical domain to near-IR wavelengths. Chalcogenide glasses (ChGs) offer high IR transparency, structural flexibility, and the ability to "tune" physical and optical properties through chemical composition and are thus ideal material candidates for integrated devices capable of sensing chemicals and biological toxins which have their spectral fingerprints in the mid-and far-infrared range [5][6]. In this paper, we describe the fabrication of optical elements and micro-channels on an integrated chip-based platform in chalcogenide glass through both lithographic processing and femtosecond laser direct writing.…”
Section: Introductionmentioning
confidence: 99%